2004
DOI: 10.1111/j.1523-1755.2004.00804.x
|View full text |Cite
|
Sign up to set email alerts
|

Ionic dialysance allows an adequate estimate of urea distribution volume in hemodialysis patients

Abstract: Anthropometric-based V values overestimate urea distribution volume calculated by DDQ and SPVV-UKM. ID allows adequate V values to be determined, and circumvents the problem of delayed postdialysis blood samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…This study, however, brings evidence that, with evaluation of V urea by SPVV and D at the same time, further evaluation of Dt/ V is close and almost equal to a reference measurement of Kt/V urea by SPVV corrected by the rebound. Di Filippo et al24,31 published similar results (Table 2). Wuepper et al 30 compared Kt/V urea by equilibrated SPVV and Dt/ V with V urea by Watson et al 32 or V urea measured by bioimpedance and found a slight difference of 0.15 (…”
supporting
confidence: 53%
“…This study, however, brings evidence that, with evaluation of V urea by SPVV and D at the same time, further evaluation of Dt/ V is close and almost equal to a reference measurement of Kt/V urea by SPVV corrected by the rebound. Di Filippo et al24,31 published similar results (Table 2). Wuepper et al 30 compared Kt/V urea by equilibrated SPVV and Dt/ V with V urea by Watson et al 32 or V urea measured by bioimpedance and found a slight difference of 0.15 (…”
supporting
confidence: 53%
“…End‐dialysis urea distribution volume (V U t) was determined using D′ cond as input to the 3‐point single‐pool variable‐volume urea kinetic model . V U t was used to estimate end‐dialysis calcium distribution volume (V Ca t) defined as anatomically equal to the extracellular fluid volume and about 1/3 of V u t. D′ cond was also used to calculate in vivo “intrinsic dialysance” for conductivity (KoA cond ) from which calcium dialysance (D′ ca ) was derived …”
Section: Methodsmentioning
confidence: 99%
“…14 End-dialysis urea distribution volume (V U t) was determined using D 0 cond as input to the 3-point single-pool variable-volume urea kinetic model. 18,19 V U t was used to estimate end-dialysis calcium distribution volume (V Ca t) defined as anatomically equal to the extracellular fluid volume and about 1/3 of V u t. D 0 cond was also used to calculate in vivo "intrinsic dialysance" for conductivity (KoA cond ) from which calcium dialysance (D 0 ca ) was derived. 20 A Donnan's factor (a) of 0.938, obtained from previously unpublished data on a HDF technique, Hemo-Filtrate Reinfusion (HFR) able to achieve diffusion and convection separately through two filters in series, 21 was used to account for the amount of plasma water diffusible Ca 2 .…”
Section: Calcium Modelingmentioning
confidence: 99%
“… spKt/V = obtained from Daugirdas equation using BUN pre‐ and post‐HD; KECN = sodium clearance read from OLC monitor display at end of HD; t = duration of HD treatment; V = TBW. Effective urea clearance estimated from OLC is represented by KECN and was previously shown to be an accurate estimate of blood‐based urea clearance K , and therefore we used KECN as K in Kt / V formula to solve for V . The same or similar approach in adults previously showed that ionic dialysance allows accurate estimation of both V and spKt/V.…”
Section: Methodsmentioning
confidence: 70%